2006
DOI: 10.1158/1535-7163.mct-05-0437
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib inhibits docetaxel-induced apoptosis via a p21-dependent mechanism in human prostate cancer cells

Abstract: Bortezomib (PS-341, Velcade) is a peptide boronate inhibitor of the 20S proteasome that is currently being combined with taxanes in several clinical trials in patients with prostate cancer. Here, we report that bortezomib inhibited docetaxel-induced M-phase arrest and apoptosis in androgen-dependent LNCaP-Pro5 cells. Direct analysis of kinase activity in immune complex kinase assays revealed that docetaxel activated cyclin-dependent kinase (CDK) 1 (CDC2) and that bortezomib blocked this activation. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 44 publications
(31 reference statements)
1
37
0
Order By: Relevance
“…However, a recent phase II trial randomizing patients to bortezomib alone or docetaxel and bortezomib, demonstrated only minor evidence of enhancement in clinical outcome (Fanucchi et al, 2006), suggesting that other determinants of sensitivity or resistance to bortezomib and docetaxel are likely to be relevant in this disease setting. One relevant factor, for example, may be bortezomib-mediated p21-dependent antagonism of docetaxel that has been reported in prostate cancer cells (Canfield et al, 2006).…”
Section: Regulation Of the Activator Bh3 Protein Bim By Bortezomibmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent phase II trial randomizing patients to bortezomib alone or docetaxel and bortezomib, demonstrated only minor evidence of enhancement in clinical outcome (Fanucchi et al, 2006), suggesting that other determinants of sensitivity or resistance to bortezomib and docetaxel are likely to be relevant in this disease setting. One relevant factor, for example, may be bortezomib-mediated p21-dependent antagonism of docetaxel that has been reported in prostate cancer cells (Canfield et al, 2006).…”
Section: Regulation Of the Activator Bh3 Protein Bim By Bortezomibmentioning
confidence: 99%
“…BAK is guarded from its activator BH3 proteins by MCL-1 (along with BCL-X L ), which directly sequesters tBID (Clohessy et al, 2006) and BIM (Gomez-Bougie et al, 2005) but also binds BAK directly, inhibiting its activation until released by free BH3-only proteins (Chen et al, 2005). The binding of tBID by MCL-1 may account for the mechanism underlying its ability to confer resistance to tumor necrosis factor-related apoptosis-inducing ligand (TRAIL; Henson et al, 2003;Taniai et al, 2004;Canfield et al, 2006). MCL-1 is targeted for polyubiquitination and proteasome-mediated degradation following DNA damage by the BH3-only protein MULE-1/ARF/LASU1 (Nijhawan et al, 2003;Warr et al, 2005;Zhong et al, 2005).…”
Section: Antagonism Of Mcl-1 By Bortezomibmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Given this mechanism, the combination of PS-341 and DTX as a cancer therapeutic regimen was evaluated in some preclinical and clinical studies. [15][16][17][18][19] However, the preclinical studies generated mixed outcomes showing that PS-341 can either enhance or antagonize DTX-induced apoptosis or antitumor activity depending on cell lines or models. 15,17 Moreover, it has been shown that the impact of PS-341 on chemotherapy (incuding DTX)-induced apoptosis or anticancer activity is sequence-or schedule-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] However, the preclinical studies generated mixed outcomes showing that PS-341 can either enhance or antagonize DTX-induced apoptosis or antitumor activity depending on cell lines or models. 15,17 Moreover, it has been shown that the impact of PS-341 on chemotherapy (incuding DTX)-induced apoptosis or anticancer activity is sequence-or schedule-dependent. 20,21 Thus, it is necessary to perform preclinical studies to carefully evaluate the efficacy of the PS-341 and DTX combination in various types of cancer to avoid a harmful combination outcome.…”
Section: Introductionmentioning
confidence: 99%